Evaluation of TG202 inhibitor for tubing steels in 15% hydrochloric acid by electrochemical noise technology. (24th December 2021) - Zhao, Mifeng; Zhang, Juantao; Hu, Fangting; Fu, Anqing; Wang, Kelin; Yin, Chengxian; Yuan, Juntao; Fan, Lei
Abstract: Acid fracturing is an effective technology for increasing oil and gas production. However, the acid will cause serious corrosion to the tubing. In this paper, the inhibition performance of the TG202 inhibitor for acidizing of high temperature and high-pressure gas wells on N80 carbon steel and 13Cr martensitic stainless-steel tubing in 15% hydrochloric acid was studied by electrochemical noise technology. The results showed that with the increase of TG202 inhibitor content, the noise resistance increased and the corrosion rate of tubing steel decreased. Under the same condition, the order of corrosion rate of tubing steels: 13Cr > HP-13Cr > N80 > P110. The pitting corrosion of HP-13Cr and 13Cr is significant. The research showed that the TG202 inhibitor had a protective effect on tubing during acidizing. The inhibition mechanism of the TG202 inhibitor was discussed.